Stromal β‐catenin overexpression contributes to the pathogenesis of renal dysplasia. Issue 2 (23rd April 2016) - Boivin, Felix J; Sarin, Sanjay; Dabas, Pari; Karolak, Michele; Oxburgh, Leif; Bridgewater, Darren
Abstract: Renal dysplasia, the leading cause of renal failure in children, is characterized by disrupted branching of the collecting ducts and primitive tubules, with an expansion of the stroma, yet a role for the renal stroma in the genesis of renal dysplasia is not known. Here, we demonstrate that expression of β‐catenin, a key transcriptional co‐activator in renal development, is markedly increased in the expanded stroma in human dysplastic tissue. To understand its contribution to the genesis of renal dysplasia, we generated a mouse model that overexpresses β‐catenin specifically in stromal progenitors, termed β‐cat GOF‐S . Histopathological analysis of β‐cat GOF ‐S mice revealed a marked expansion of fibroblast cells surrounding primitive ducts and tubules, similar to defects observed in human dysplastic kidneys. Characterization of the renal stroma in β‐cat GOF ‐S mice revealed altered stromal cell differentiation in the expanded renal stroma demonstrating that this is not renal stroma but instead a population of stroma‐like cells. These cells overexpress ectopic Wnt4 and Bmp4, factors necessary for endothelial cell migration and blood vessel formation. Characterization of the renal vasculature demonstrated disrupted endothelial cell migration, organization, and vascular morphogenesis in β‐cat GOF ‐S mice. Analysis of human dysplastic tissue demonstrated a remarkably similar phenotype to that observed in our mouse model, including altered stromal cell differentiation, ectopic Wnt4 expression in the stroma‐like cells, and disrupted endothelial cell migration and vessel formation. Our findings demonstrate that the overexpression of β‐catenin in stromal cells is sufficient to cause renal dysplasia. Further, the pathogenesis of renal dysplasia is one of disrupted stromal differentiation and vascular morphogenesis. Taken together, this study demonstrates for the first time the contribution of stromal β‐catenin overexpression to the genesis of renal dysplasia. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.